Presence of a genetic association between NRG-3 SNP rs17101193 and schizophrenia - Mert Sozen, Mustafa; Acar, Ceren; Kartalci, Sukru (Annals of Medical Research, 2021)
Aim: NRG-3 gene is a member of neuregulin signaling pathway and alleles of several single nucleotide polymorphisms (SNP) located in this gene are suspected to be associated with schizophrenia. During this work, we have done a study to investigate the potential association of the SNP rs17101193 of NRG-3 gene.Material and Methods: We used the DNA samples from 301 unrelated schizophrenia patients and 326 healthy control samples collected from Malatya-Turkey to determine the SNP genotypes. After genotyping, we compared the genotypes and alleles in terms of distributions between cases and controls. We also applied the recessive models for both alleles to get a more clarified result. We used Chi-Squared test and Fisher’s exact test for hypothesis testing.Results: Even though the difference between the case and control groups were not significant in context of distributions of two alleles of rs17101193, the distributions of genotypes were significantly different (p = 0.046). On the other hand, one of the genotypes (AA) was seen only in the patients. Conclusion: The results of our analyses and statistical test indicated that rs17101193 SNP of NRG-3 gene has a potential to be associated with schizophrenia and homozygosity of “A” allele seems to be a risk factor in our population. More evidence from separate case-control studies from different populations may be required to strengthen this idea.